PERBEDAAN EFEKTIFITAS PEMBERIAN MINYAK ZAITUN (OLIVE OIL) DAN MINYAK KELAPA MURNI (VIRGIN COCONUT OIL) TERHADAP PENYEMBUHN RUAM PADA POPOK BAYI DI KLINIK TAHUN 2023 - Hutabarat, Vitrilina - (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2023)
Babies will be sensitive to everything around them. Babies have relatively thin skin, making them susceptible to infection, inflammation and allergies. One of the most common skin problems is diaper rash. Diaper rash appears on the baby's thighs and buttocks. Causes of diaper rash include poor skin hygiene, severe hot flashes, and diarrhea. OBJECTIVE: To find out whether there is a difference in the effect between olive oil and coconut oil in healing diaper rash in babies. METHODS: This study used a two-group design with a quasi-experimental style, before and after a test-control design. The study population consisted of babies aged 0-12 months who suffered from diaper rash in Kasih Ibu, Deli Tua District, Deli Serdang Regency, who had an average of 17 visits. Non-random sampling and targeted sampling using the Federer formula were used in this sample, with a total sample size of 16 people. An observation sheet with the Mann-Whitney test was used as an instrument. RESULTS: The results of the bivariate analysis test using Mann-Whitney showed that the average value for giving olive oil was (1.75) from 8 samples and for giving pure coconut oil, it was (1.25) with an average difference of (50). ) with Z count for giving olive oil (2.936) and giving muri coconut oil (0.3032). Based on the results of the Mann-Whitney test, the p-value was 0.023. Because the p-value <0.05, it can be concluded that there is a significant difference between the use of olive oil and pure coconut oil for healing diaper rash in babies at the Kasih Ibu Clinic, Deli Tua District, Deli Serdang Regency in 2023 Suggestion: In the future, it is hoped that research will be more advanced and the results will be enriched by looking for other treatments that can be used to reduce the severity of diaper rash, such as giving aloe vera or honey.